Connecting quantum dots with enzymes: mediator-based approaches for the light-directed read-out of glucose and fructose oxidation. Issue 8 (3rd February 2017) - Riedel, M.; Sabir, N.; Scheller, F. W.; Parak, W. J.; Lisdat, F.
Abstract : We report on strategies to build up enzyme/nanoparticle hybrid systems on electrodes in order to combine the biocatalytic features with the unique photophysical properties of QDs. Abstract : The combination of the biocatalytic features of enzymes with the unique physical properties of nanoparticles in a biohybrid system provides a promising approach for the development of advanced bioelectrocatalytic devices. This study describes the construction of photoelectrochemical signal chains based on CdSe/ZnS quantum dot (QD) modified gold electrodes as light switchable elements, and low molecular weight redox molecules for the combination with different biocatalysts. Photoelectrochemical and photoluminescence experiments verify that electron transfer can be achieved between the redox molecules hexacyanoferrate and ferrocene, and the QDs under illumination. Since for both redox mediators a concentration dependent photocurrent change has been found, light switchable enzymatic signal chains are built up with fructose dehydrogenase (FDH) and pyrroloquinoline quinone-dependent glucose dehydrogenase ((PQQ)GDH) for the detection of sugars. After immobilization of the enzymes at the QD electrode the biocatalytic oxidation of the substrates can be followed by conversion of the redox mediator in solution and subsequent detection at the QD electrode. Furthermore, (PQQ)GDH has been assembled together with ferrocenecarboxylic acid on top of the QD electrode for the construction of a funtional biohybrid architecture, showing that electron transfer can be realized from the enzyme over the redox mediator to the QDs and subsequently to the electrode in a completely immobilized fashion. The results obtained here do not only provide the basis for light-switchable biosensing and bioelectrocatalytic applications, but may also open the way for self-driven point-of-care systems by combination with solar cell approaches (power generation at the QD electrode by enzymatic substrate consumption).